2023
DOI: 10.1186/s12933-023-01985-3
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning in precision diabetes care and cardiovascular risk prediction

Evangelos K. Oikonomou,
Rohan Khera

Abstract: Artificial intelligence and machine learning are driving a paradigm shift in medicine, promising data-driven, personalized solutions for managing diabetes and the excess cardiovascular risk it poses. In this comprehensive review of machine learning applications in the care of patients with diabetes at increased cardiovascular risk, we offer a broad overview of various data-driven methods and how they may be leveraged in developing predictive models for personalized care. We review existing as well as expected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 138 publications
(146 reference statements)
0
11
0
Order By: Relevance
“…Previous studies utilizing logistical regression and classification trees have predicted that fasting blood glucose, BMI, and age are the main predictors of developing diabetes and observed population health risk assessment for diabetes onset [25][26][27]. It has also been used to predict associated complications [28,29]. However, there remains a gap in the literature when it comes to analyzing outcomes and readmission with the use of machine and deep learning.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies utilizing logistical regression and classification trees have predicted that fasting blood glucose, BMI, and age are the main predictors of developing diabetes and observed population health risk assessment for diabetes onset [25][26][27]. It has also been used to predict associated complications [28,29]. However, there remains a gap in the literature when it comes to analyzing outcomes and readmission with the use of machine and deep learning.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review [9] has highlighted that artificial intelligence (AI) and machine learning are catalyzing a transformative shift in medicine, offering data-driven, personalized approaches for addressing diabetes and its associated cardiovascular risk. Research has revealed that the utilization of AI and data-driven techniques in managing patients with diabetes who face heightened cardiovascular risks shows great promise.…”
Section: Introductionmentioning
confidence: 99%
“…Research has revealed that the utilization of AI and data-driven techniques in managing patients with diabetes who face heightened cardiovascular risks shows great promise. These approaches can be harnessed to develop predictive models aimed at personalized care, encompassing diagnosis, prognosis, phenotyping, and treatment of both diabetes and its cardiovascular complications [9]. .…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes has also been studied using machine learning [7][8][9]. Oikonomou et al [10] provide a comprehensive overview of how machine learning has been applied to precision diabetes care, particularly in cardiovascular risk prediction among diabetic patients. Their work underscores the significant potential of machine learning in transforming diabetes care by leveraging large datasets to identify risk factors and predict outcomes with high accuracy.…”
Section: Introductionmentioning
confidence: 99%